Double Transseptal Puncture for Catheter Ablation of Atrial Fibrillation: Safety of the Technique and Its Use in the Outpatient Setting - Laurent M. Haegeli; Thomas Wolber; Ercüment Ercin; Lukas Altwegg; Nazmi Krasniqi; Paul G. Novak; Laurence D. Sterns; Corinna B. Brunckhorst; Thomas F. Lüscher; Richard A. Leather; Firat Duru (Cardiology Research and Practice)
Introduction. For pulmonary vein isolation in patients with atrial fibrillation (AF), some centers use the double transseptal puncture technique for catheter access in order to facilitate catheter manipulation within the left atrium. However, no safety data has so far been published using this approach. Method. 269 ablation procedures were performed in 243 patients (mean age 56.6±9.3 years, 75% men) using the double transseptal puncture for catheter access in all cases. Patients were considered for ablation of paroxysmal (80%), persistent (19%), and permanent (1%) AF. 230 procedures were performed on an outpatient basis (85.5%), and 26 were repeat procedures (9.7%). Results. The double transseptal puncture catheter access was successfully achieved in all patients. The procedural success with the endpoint of pulmonary vein isolation was reached in 255 procedures (95%). A total of 1048 out of 1062 pulmonary veins (99%) were successfully isolated. Major complications occurred in eight patients (3.0%). Of these, seven patients (2.6%) had pericardial effusion requiring percutaneous drainage, and one patient (0.4%) suffered a minor reversible stroke. One patient (0.4%) had a minor air embolism with transient symptoms. Conclusion. The double transseptal puncture catheterization technique allows easy catheter manipulation within the left atrium to reach the goal of acute procedural success in AF ablation. Procedure-related complications are rare, and the technique can be used safely for AF ablation in the outpatient setting.